Associations of physical activity and sleep with mental health during and post-COVID-19 pandemic in chinese college students: a longitudinal cohort study - Haonan Wang; Yixiao Ding; Yinghong Dai; Zilin Fan; Shubo Wen; Xinying Wang; Jie Yuan; Yibo Wu; Liang Yu (Comprehensive Psychiatry)
Background: The COVID-19 pandemic seriously impacted people's lifestyles, leading to changes in physical activity, sleep and mental health. This study aimed to assess the recovery of these indicators in Chinese university students post-COVID-19 pandemic, and explore the association between lifestyle changes and psychological problems. Methods: A two-wave longitudinal study was conducted with 2,748 college students in Hebei, China. Self-report questionnaires measured physical activity, sleep and psychological variables (depression symptoms, anxiety symptoms, and perceived stress) in 2022 and 2024. McNemar chi-square test compared differences between the two waves. Additionally, univariate and multivariate logistic regression analyses were performed to examine the independent and joint associations between changes in lifestyle behaviors and psychological problems across this period. Results: Proportion of physical inactivity decreased from 22.5% to 16.2%, and poor sleep quality reduced from 18.3% to 16.2% after the pandemic (P < 0.05). Depression symptoms and anxiety symptoms also improved (P < 0.05), while perceived stress remained high (64.5%). Compared to consistently inactive students, those becoming physically active (depression OR = 0.40, anxiety OR = 0.34, stress 0.56) and those persistently active (depression OR = 0.43, anxiety OR = 0.38, stress 0.47) had reduced psychological symptoms. However, after adjusting for confounders, the association between improved physical activity and mental health problems was insignificant (P > 0.05). Improved sleep (depression OR = 0.42, anxiety OR = 0.24, stress 0.42) and consistently good sleep (depression OR = 0.20, anxiety OR = 0.20, stress 0.37) also demonstrated a protective effect after fully adjusting for demographics and socioeconomic status. Conclusions: This study found that high perceived stress persisted. Although physical activity improved across this period, its change was not significantly associated with mental health after adjustments. However, improved sleep quality was significantly associated with reductions in depression levels, anxiety levels, and perceived stress. These findings highlight the importance of sleep and physical activity in mental health recovery post-pandemic and the need for targeted interventions.